Land snail microclimate niches identify suitable areas for climate refugia management on a montane landscape - Michael K. Lucid (Elsevier, 2021)
Climate refugia management is an emerging natural resource sub-discipline but identifying which species would benefit, their climatic requirements, and where both species and suitable conditions are located remains problematic. Land snails have species specific temperature needs and are one of the most imperiled groups of animals. The goal of our study was to 1) determine the distribution of land snails across a large 22,975 km2 study area in North America’s Pacific Northwest, 2) determine if microclimate, macroclimate, or non-microclimate variables influence species occurrence, and 3) identify microrefugia and clusters of microrefugia most suitable for land snail climate refugia management. From 2010 to 14, we stratified our study area into 5×5 km sampling cells and co-located land snail surveys with air temperature data loggers at 1–2 sites per cell for a total of 830 survey sites. We used our air temperature data to calculate standard microclimate variables and generated Random Forest models which evaluated 8 microclimate, 2 macroclimate, and 4 non-microclimate variables for 27 land snail species. Climate variables outperformed non-climate variables and we identified land snail species which occupy ‘cool’ (n = 12), ‘warm’ (n = 7), or ‘generalist’ (n = 8) microclimate niches. We developed a microclimate scoring system which we used to map cool microsites and identify the largest cluster in each of the five mountain ranges spanning our study area. We recommend these areas be prioritized for land snail climate refugia management.